2011
DOI: 10.1371/journal.pone.0025051
|View full text |Cite
|
Sign up to set email alerts
|

Esophagitis in a High H. pylori Prevalence Area: Severe Disease Is Rare but Concomitant Peptic Ulcer Is Frequent

Abstract: BackgroundFew data are available on the prevalence of erosive and severe esophagitis in Western countries.ObjectiveTo retrospectively determine the prevalence and the factors predicting erosive esophagitis and severe esophagitis in a large series of endoscopies in Spain.DesignRetrospective observational study. A multivariate analysis was performed to determine variables predicting severe esophagitis.SettingDatabases of 29 Spanish endoscopy units.PatientsPatients submitted to a diagnostic endoscopy during the y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Furthermore, many factors that might influence the development of these diseases – for example, the type of predominant diet, tobacco or alcohol consumption, or proton pump inhibitor (PPI) use – have been steadily changing in recent years. A previous retrospective study by our group found the prevalence of esophagitis to be low, appearing in only 8.7% of 93,699 endoscopies reviewed 9 …”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…Furthermore, many factors that might influence the development of these diseases – for example, the type of predominant diet, tobacco or alcohol consumption, or proton pump inhibitor (PPI) use – have been steadily changing in recent years. A previous retrospective study by our group found the prevalence of esophagitis to be low, appearing in only 8.7% of 93,699 endoscopies reviewed 9 …”
Section: Introductionmentioning
confidence: 77%
“…A previous retrospective study by our group found the prevalence of esophagitis to be low, appearing in only 8.7% of 93,699 endoscopies reviewed. 9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation